Application of Theiler’s murine encephalomyelitis virus in treatment of multiple sclerosis - Li, Lin; Zhou, Rui; Sun, Lin (Frontiers in Microbiology, 2024)
Theiler's murine encephalomyelitis viruse (TMEV) infected mice have been often used as an animal model for Multiple sclerosis (MS) due to their similar pathology in CNS. So far, there has been no effective treatment or medicine to cure MS completely. The drugs used in the clinic can only reduce the symptoms of MS, delay its recurrence, and increase the interval between relapses. MS can be caused by many factors, and clinically MS drugs are used to treat MS regardless of what factors are caused rather than MS caused by a specific factor. This can lead to inappropriate medicine, which may be one of the reasons why MS has not been completely cured. Therefore, this review summarized the drugs investigated in the TMEV-induced disease (TMEV-IDD) model of MS, so as to provide medication guidance and theoretical basis for the treatment of virus-induced MS.